Radiotherapy dosimetry and radiotherapy related complications of immediate implant-based reconstruction after breast cancer surgery - Zhang, Yu; Ye, Fuxiu; Teng, Yun; Zheng, Jin; Li, Chunlu; Ma, Ruilan; Zhang, Haichen (Frontiers in Oncology, 2023)
Backgrounds:The impact of immediate implant-based breast reconstruction (IBBR) on the delivery of radiotherapy plans remains controversial. This study aimed to compare the differences in radiotherapy dosimetry, complications of radiotherapy, and quality of life in patients who underwent modified radical mastectomy combined with or without IBBR.We retrospectively collected 104 patients with breast cancer who underwent intensitymodulated radiation therapy after modified radical mastectomy with IBBR (n =46) or not (n =58) from January 2017 to December 2021. The dosimetric differences in radiotherapy of planning target volume (PTV) and organs at risk and the differences in complications of radiotherapy between the two groups were compared.We also applied the functional assessment of cancer therapy-breast cancer (FACT-B) score to compare the difference in quality of life. The chi-square test and independent samples t-test were used to analyze the above data.Results: IBBR group was associated with higher PTV volumes, PTV D98, V95, and lower PTV Dmean, D2 compared with the non-reconstruction group (P<0.05). IBBR group also had lower radiotherapy dosimetric parameters in the ipsilateral lung and the heart of left breast cancer patients.The differences in the rates of radiation pneumonia (RP) and radiation dermatitis (RD) between the two groups were not statistically significant (P > 0.05). Moreover, FACT-B scores at 6 months after radiotherapy in patients with IBBR were higher than those without reconstruction (P < 0.05).Patients with IBBR achieved better radiation dosimetry distribution and higher quality of life without more complications of radiotherapy.